Design Of The Sharia Insurance Study Program Research Roadmap: R&D Model - Atika Atika; Nurul Jannah; Nurul Inayah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The significance of the research roadmap's position within the study program stems from the fact that it serves as a guide, control, and assurance of the research quality for lecturers and students. Obtaining a research roadmap development design for the sharia insurance study program is the objective of this investigation. This research employs a qualitative approach. Qualitative analysis was employed to examine the data utilizing the 4D model in conjunction with the R&D (Research and Development) method. The research findings indicate that the formulation of the Research Roadmap Design for the Sharia Insurance Study Program was influenced by the following factors: the Scientific Vision of the program, the Field of Expertise of the Lecturers, ARKAN, industry needs and graduate profiles, and research topics conducted by both students and faculty. The research conducted by lecturers at Homebase remains below 50% compliant with the research roadmap outlined for the sharia insurance study program. The research road map indicates that fifty percent of students have completed sharia insurance study programs; however, a substantial amount of research remains that centers on the identical subject matter. Consequently, further deliberation is required to select and disseminate the remaining themes outlined in the research roadmap for sharia insurance study programs